2015
DOI: 10.1016/j.ejrnm.2014.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Role of transvaginal ultrasonography and colour Doppler in the evaluation of postmenopausal bleeding

Abstract: Aim of the work: The aim of this study is to evaluate the role of transvaginal ultrasonography and colour Doppler in postmenopausal bleeding. Patients and methods: In the study fifty female patients with their age ranging between 45 and 80 years were subjected to transvaginal US examination and transvaginal colour and pulsed Doppler examination. Results: All the malignant cases and 94.7% of the benign cases had endometrial thickness P5 mm, however 90% of the control group with the remaining of the benign cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
(15 reference statements)
1
6
0
Order By: Relevance
“…15 Similarly A study conducted Abdel Maboud et al in which 50 cases were reported with abnormal uterine bleeding, 35 out of 50 cases were benign endometrial lesions causing abnormal uterine bleeding carcinoma were reported in about 15 cases. 16 So our findings are similar with the findings of this study.…”
Section: Discussionsupporting
confidence: 92%
“…15 Similarly A study conducted Abdel Maboud et al in which 50 cases were reported with abnormal uterine bleeding, 35 out of 50 cases were benign endometrial lesions causing abnormal uterine bleeding carcinoma were reported in about 15 cases. 16 So our findings are similar with the findings of this study.…”
Section: Discussionsupporting
confidence: 92%
“…In the literature, the values of UtA_RI and PI in the malignant group were often lower than those in the benign group [24][25][26][27][28][29][30][31][32][33]. Table 3 shows that, in our study, there was a difference in UtA_RI between the benign and malignant groups.…”
Section: Discussionmentioning
confidence: 43%
“…Similar to the study by AbdelMamoud and Elsaid. [ 25 ], all cases of malignant endometrial disease had an ET greater than 5 mm ( P <0.05). In particular, we found seven cases of invasive lesions without identification of ET.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence sample size of 50 is taken; which is same as some other studies. [7][8][9] Patients fulfilling the eligibility criteria will be followed up from admission to discharge. Necessary information will be collected in predesigned data sheet and finally findings will be compiled and analyzed using statistical analysis.…”
Section: Methods and Size Samplingmentioning
confidence: 99%